FORMATION OF READING CULTURE AMONG PRIMARY SCHOOL STUDENTS - Muhammadjonova Farangizbegim Ma’mirjon qizi; G’ulomjonova Mubdi’ma G‘ayratjon qizi; Nabiyeva Rohilaxon Erkinjon qizi (Scholar Express Journal, 2024)
This article deals with the formation of reading culture among primary school students, educating them in the spirit of reading. Students were informed about the importance of reading lessons in the formation of the skills of correct use
Keywords: source of spirituality; sense of love; sense of responsibility